(untitled) (Interdisciplinary Research in Education, 2022)
The rate of return to education is the sum of discounted benefits and costs. It shows the relatively profitable sector for a secure investment. The main objective of this study is to review and analyze the volume of the rate of return to education. The literature review, survey design was used, and the materials were collected using purposive sampling. The analysis concludes that the rate of return on education can be analyzed based on the additional year of schooling, sex, levels of education, occupations, geographical regions, countries, and sectors. Different studies conducted in different countries reveal that the size of the rate of return differs according to the categories mentioned above. It means that overall returns to education seem highly heterogeneous. Likewise, most studies show that the private rate of returns for females is higher than that of males; the tertiary level’s returns are higher than the other levels, and the urban sector’s returns are higher than that of the rural sector.